HARGA DAN SUASANA TOKO (STORE ATMOSPHERE) DALAM MENENTUKAN KEPUASAN KONSUMEN DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA COFFEE SHOP TITIK KUMPUL CAPORE SITUBONDO - Adhinda, Elok Gita; Arief, Mohammad Yahya; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2022)
Lifestyle phenomena, especially young people who tend to like to hangout or hang out together in cafes which is a form of globalization demands that have a significant impact on people's way of life. Not only to be used as a place to hangout or hang out, cafÃ© is also a place or a place to express aspirations and ideas. The purpose of this study was to analyze and examine of Price and Store Atmosphere on Consumer Satisfaction at the Coffee shop Titik Kumpul Capore Situbondo through Consumer Trust. This research is an explanatory research. The population in this study were consumers at the Coffee shop Of Capore Situbondo Titik Kumpul. The sampling technique is determined by probability sampling by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The result of the analysis using the smart partial least square (PLS) 3.0 software, show that price has a significant positive effect on Consumer Confidence. Store Atmosphere has a significant negative effect on Consumer Confidence. Price and Store Atmosphere have a significant positive effect on Consumer Satisfaction. Consumer Trust has a significant positive effect on Consumer Satisfaction. Price for Consumer Satisfaction through Consumer Trust has a significant positive effect. Store Atmosphere on Consumer Satisfaction through Consumer Trust has a positive but insignificant effect.